Benompl and mancozeb as fungicides in soil studies of Azotobacter and Beijeninckia - Ayanaba, A. (1981)
Routine media containing 0.005% each of benomyl and mancozeb for the enumeration and isolation of Azotobacter and Beijerinckia in soil studies are described. The incorporation of these fungicides in routine media was found to be more effective in inhibiting fungal contaminants than the use of cycloheximide.